Influence Of Deep Cryogenic Processing On Carbide Grain Size In Sintered Carbide WC-Co - Průcha, Vojtěch; Jansa, Zdeněk; Veselý, Vilém (Manufacturing Technology Journal, 2021)
The paper deals with the change in carbide grain size of sintered WC-Co carbide after cryogenic pro-cessing. Because this structural parameter has a significant effect on mechanical properties. Some sources indicate that due to cryogenic processing takes place to reduce the size of carbide grains and other sources indicate that takes place to increase the size of carbide grains. Measurement of the grain size can be performed using several methods. In this paper, a comparative method according to the ASTM B 390 standard was used. Further, the linear intersection method according to the ČSN ISO 4499-2 standard was used. The last one for measuring the grain size the image analysis software NIS - Elements AR v. 4.40 was used. Also, the size of the WC crystallites by XRD was measured. Crystallites are coherent diffraction domains in X-ray diffraction. The results show that due to cryo-genic processing, the carbide grain increases but the size of the WC crystallites was decreasing.
Keywords: Grain Size; Crystallites; WC; Image Analysis; Deep Cryogennic Treatment